2021
DOI: 10.21037/qims-20-978
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram based on multiparametric magnetic resonance imaging and elastography-derived data for the stratification of patients with prostate cancer

Abstract: Background: This study sought to develop and validate a nomogram combining the elastographic Q-analysis score (EQS), the Prostate Imaging Reporting and Data System (PI-RADS) score, and clinical parameters for the stratification of patients with prostate cancer (PCa). Methods: A retrospective study was conducted of 375 patients with 375 lesions who underwent volumenavigation transrectal ultrasound (TRUS) and multiparametric magnetic resonance imaging (MP-MRI)fusion targeted biopsies between April 2017 and Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Wang 26 et al combined PI-RADS score with PSAD to detect clinically significant prostate cancer, the specificity and positive predictive values of which were 93.5% and 82.4%, respectively. Ding 27 et al combined PI-RADSv2 score and ultrasonic elastography-derived data to stratify prostate cancer, and found that the nomogram they constructed combing elastography-derived and mp-MRI data was more clinically useful than the model based on PI-RADS score and clinical parameters alone.…”
Section: Discussionmentioning
confidence: 99%
“…Wang 26 et al combined PI-RADS score with PSAD to detect clinically significant prostate cancer, the specificity and positive predictive values of which were 93.5% and 82.4%, respectively. Ding 27 et al combined PI-RADSv2 score and ultrasonic elastography-derived data to stratify prostate cancer, and found that the nomogram they constructed combing elastography-derived and mp-MRI data was more clinically useful than the model based on PI-RADS score and clinical parameters alone.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included studies used a threshold of PI-RADS ≥3, but several studies used PI-RADS ≥4. According to PI-RADS v.2 ( 36 ), a score of 3 means that PCa is suspected, whereas a score of 4 means that cancer is more likely. In addition, we showed that the diagnostic sensitivity of PI-RADS ≥3 (93%; 95% CI: 90–96%) was higher than that of PI-RADS ≥4 (85%; 95% CI: 77–93%).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fusion of these imaging modalities was associated with even higher sensitivity (97%), specificity (88%), PPV (85%), and NPV (95%). Furthermore, the same researchers developed and then validated a nomogram combining the elastographic Q analysis score, PI-RADS score, and clinical parameters for the stratification of patients with PCa [117]. The areas under the curve for predicting csPCa in the training cohort (n = 271) and in the validation cohort (104) were 0.936 (95% CI 0.906-0.965) and 0.971 (95% CI 0.9331-1), respectively.…”
Section: Future Perspectivesmentioning
confidence: 99%